Morbidity pattern in the school going adolescent girls of rural and urban Prayagraj, Uttar Pradesh - Dabas, Nitisha; Prakash, Shiv; Parveen, Khurshid; Singh, Richa (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescence is an intermediary phase from childhood to adulthood and is a very delicate phase of life. WHO has defined Adolescence as the period between 10-19 years of life. Among adolescents, girls constitute a more vulnerable group, particularly in developing countries, where they are traditionally married at an early age and are exposed to greater risk of reproductive morbidity and mortality. Nutritional deficiency disorders (stunting, wasting), menstrual disorders, mental health problems etc. appear as serious problem during this stage. The study was done with objective to assess the morbidity pattern in school going adolescent girls in Urban and Rural Prayagraj. Methods: A school based cross-sectional study was carried out in Prayagraj district. Study participants were 800 adolescent girls, 400 urban and 400 rural of age groups 10–19 years studying in class 6th to 12th. The data was collected by using predesigned, pretested, semi structured questionnaire and analyzed by using SPSS 21.0 version. Results: It was observed that most prevalent morbidity in rural and urban school going adolescent girls were dysmenorrhoea 381 (47.6%), pallor 296 (37%), psychological problems 325 (40.6%) and ocular diseases 191 (23.8%). Other morbidities were hypertension, dental problems, overweight/obesity, skin diseases, ear diseases, respiratory diseases, gastrointestinal diseases and injury. Conclusions: Out of 800 study participants, 275 adolescent girls were having morbidity. Significant difference in proportion of morbidities was found among rural and urban adolescent girls with ear diseases, eye diseases, pallor, dysmenorrhoea, overweight/obesity and hypertension.